2020
DOI: 10.1038/s41598-020-67721-z
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of deception in a social context: an fMRI replication study

Abstract: z www.nature.com/scientificreports/ zero. As no significance test is performed, no correction for multiple comparisons is required. Additionally, no effect size threshold is necessary to apply in the Bayesian approach 75. In the present study, a voxelwise analysis for pairs and groups of contrasts was performed using a zero effect size threshold (same as applied in the paper by Volz et al. (2015)) and a PPM threshold defined as log-odds threshold > 3. Xjview Toolbox (https ://www.alive learn .net/xjvie w/) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
1
12
0
1
Order By: Relevance
“…For example, one study (e.g., Yin & Weber, 2019), using the spontaneously lying strategy, incentivized by relatively high payoffs (honesty: $1, lying: $8, lying got caught: -$6) and low (probability = .2) caught-up rates, did not find the involvement of ToM network (see also Lisofsky et al, 2014, for meta-analysis results). Second, another mono-fMRI study (Volz et al, 2015;Zheltyakova, Kireev, Korotkov, & Medvedev, 2020), investigating lying in the social context through the inquiry of honest answers, and simple and sophisticated deceptions after each sender-receiver trial, did not find the executive/inhibition subnetwork in their GLM contrasts. Third, some recent fNIRS hyperscanning studies, through more naturalistic task designs (e.g., bluffing card game, and sender-receiver games) (Chen et al, 2020;Wang et al, 2020;Zhang et al, 2017), revealed both ToM and inhibition subnetworks, but was unable to probe into reward-related network (e.g., caudate nucleus), due to the depth limitation of NIRS (Ferrari & Quaresima, 2012;Pinti et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…For example, one study (e.g., Yin & Weber, 2019), using the spontaneously lying strategy, incentivized by relatively high payoffs (honesty: $1, lying: $8, lying got caught: -$6) and low (probability = .2) caught-up rates, did not find the involvement of ToM network (see also Lisofsky et al, 2014, for meta-analysis results). Second, another mono-fMRI study (Volz et al, 2015;Zheltyakova, Kireev, Korotkov, & Medvedev, 2020), investigating lying in the social context through the inquiry of honest answers, and simple and sophisticated deceptions after each sender-receiver trial, did not find the executive/inhibition subnetwork in their GLM contrasts. Third, some recent fNIRS hyperscanning studies, through more naturalistic task designs (e.g., bluffing card game, and sender-receiver games) (Chen et al, 2020;Wang et al, 2020;Zhang et al, 2017), revealed both ToM and inhibition subnetworks, but was unable to probe into reward-related network (e.g., caudate nucleus), due to the depth limitation of NIRS (Ferrari & Quaresima, 2012;Pinti et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…All the included participants had more than two runs and the average success rate in following the given task instructions (to tell the truth/lie) was higher than 75% (Figure S2). In this study, the number of included participants is comparable with prior fMRI studies testing on deceptions (Bhatt et al, 2009;Ganis, Rosenfeld, Meixner, Kievit, & Schendan, 2011;Nuñez et al, 2005;Yin & Weber, 2019;Zheltyakova, Kireev, Korotkov, & Medvedev, 2020).…”
Section: Participantsmentioning
confidence: 90%
“…A recent study showed a positive correlation between the level of self-consciousness and the GMV of the precuneus (Morita et al, 2021). This region has also been found to be associated with social-cognitive processes in the setting of deceptive behavior (Lisofsky et al, 2014;Volz et al, 2015;Kireev et al, 2017;Zheltyakova et al, 2020) as well as moral cognition (Fede and Kiehl, 2019). ToM can be fractioned into cognitive and affective domains; the cognitive domain is more likely to be included in the SI concept.…”
Section: Discussionmentioning
confidence: 99%